ANALYSIS OF ADVERTISING TEXTS IN TRANSLATION - Inomjonova Gulchehra Anvarjon qizi; Batirova Xurshida Egamberdiyevna (PEDAGOGS, 2024)
Abstract. Advertising is a special form of communication, which refers to the process of conveying promotional messages about products, services or brands to a target audience through various media channels. Advertising information can be regarded as mass information, as an economic tool and as a psychological influence. This article delves into the complicated process of translating English advertising into uzbek, aiming to exploring challenges and strategies involved in cross-cultural communication within the realm of advertising. Through analyzing various techniques and cultural nuances, this article offers insights into adapting ads for uzbek audience who can gain knowledge about advertised stuff while watching.